Analysing the Impact of Third-Party Involvement on Smooth Distribution in Supply Chain in Indonesia - Darmiono, Darmiono (Yayasan Sinergi Kawula Muda, 2023)
Businesses must ensure that commodities are distributed smoothly throughout supply chains in order to effectively satisfy client needs. It is quite difficult to provide smooth distribution in Indonesia due to its diversified topography and infrastructure issues. A crucial element impacting the effectiveness of distribution is the participation of other parties, like logistics suppliers and middlemen. The purpose of this study is to examine how third parties' involvement affects Indonesian supply chains' ability to distribute commodities efficiently. A quantitative approach is used to collect and analyze data, with the use of surveys and statistical techniques. A strong positive association between the degree of third-party involvement and distribution efficiency is seen in the findings, highlighting the significance of forming strategic alliances with third-party logistics providers. The report offers suggestions for improving distribution efficiency as well as insights into Indonesian supply chain dynamics.